PELANGGARAN PRINSIP KESANTUNAN BERBAHASA DALAM FILM TULLAH - Elvira, Suci (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The purpose of this research to describe violations of the principle of linguistic politeness, implicatures appear, and the principle of irony in the Tullah’s movie. This study uses qualitative research in descriptive form. Data collection techniques using documentary, notes, and translations. The data in this study is a dialogue or monologue in the Tullah’s movie, while the source of the data is the Tullah’s movie. Based on the results of data analysis the violation of the most widely performed by the cast in the Tullah’s movie is a violation of the agreement maxims totaling 57. Implicatures appear in the Tullah’s movie were 17, implicatures that often arises is implicatures request amounting to 11, followed by other implicatures. The principle of irony in Tullah’s movie numbered 4. The suggestion of this study is expected to be a reference for further research, become a reference and guide readers in speaking in public to be a virtuous person and manners, and can be input for the teaching of Indonesian so that the public school environment can figure out how to talk polite with other. Keywords: Politeness Violation, Implicature, Irony, Tullah’s Movie, Sambas Malay